The strategy and tactics of pricing : a guide to growing more profitably - Nagle, Thomas T., 1951- (New York Routledge, 2018)
"The Strategy and Tactics of Pricing is the most well-established and influential strategic pricing text available, relied on by practitioners and students globally as a core guide for value-based pricing. The book explains how to balance the ability to create and extract value through from markets by managing pricing decisions in a more strategic and profitable manner. Rather than calculating prices to cover costs or to achieve sales goals, readers will learn to frame more strategic choices that proactively influence customer perceptions of value, manage internal costs, and profitably shift demand curves. This edition features new discussions on harnessing concepts from behavioral economics as well as a refined "value cascade" to help organize the topics covered in this book. Readers will also benefit from: -Major revisions to more than a third of the chapters, including an expanded discussion of the role of artificial intelligence and machine learning analytics tools to assist in the evaluation of new pricing opportunities -Discussion of many of the new pricing and revenue-recognition models such as consumption-based pricing, outcomes-based pricing, and others -An expanded discussion on "Special Topics in Pricing" that cover many of the transformative pricing moves successful companies have made in the past few years in response to major disruptive forces such as the pandemic as well as re-emergent inflation -In-chapter textboxes and call-0ut to highlight different "pricing concepts in action" using actual examples of companies addressing market challenges. -Chapter summaries and visual aids to help the reader better understand the ideas and concepts presented throughout this book. This comprehensive, managerially-focused text is a must-read for students and professionals with an interest in strategic price management and achieving commercial excellence for their organizations. Additional online resources include PowerPoint slides and an instructor's manual, including exercises, mini-cases, and examination questions"--
Thomas Nagle appears as first named author on earlier editions.
Includes bibliographical references and index.
Keywords: Pricing; Marketing -- Decision making